Is the full diffusion of EU standards optimal for the development of the food sectors in the CEEC? The case of the polish dairy sector - Hockmann H.; Pieniadz A. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
The challenge of implementing EU quality and safety standards of food production and trading is one of the main forces driving the restructuring of agro-food chains in Central and Eastern European Countries (CEEC). The progress made in the compliance process varies between sectors and countries due to differences in national policies, market structure, and the complexity of requirements in the individual sectors. We combine two approaches, diffusion models and mechanism design, to explain the current situation in the Polish milk chain. We argue that adoption and enforcement decisions in the food chain are determined by economic considerations of farmers and processors. Factors such as a changing institutional environment, control principles, pricing behaviour, screening mechanisms and market structure, ail of which influence adoption of standards, are identified and discussed. The findings are used to answer the question of whether the complete diffusion of standards is optimal for the development of the Polish dairy sector. Similar results hold for other food sectors in Roland and in other CEEC.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)